2017
DOI: 10.1212/cpj.0000000000000375
|View full text |Cite
|
Sign up to set email alerts
|

Mild brain injury and anticoagulants

Abstract: Systematic routine use of a second CT scan in mild head trauma in patients taking anticoagulants is expensive and clinically unnecessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 39 publications
4
15
2
Order By: Relevance
“…Several of these examinations already have established referral criteria or have recommendations against them in the Choosing Wisely list, however this review show that these are still being used in clinical practice, and more examinations might need referral guidelines. The most commonly practices reported as low-value was head CT in several clinical queries (especially related to minor head injury [ 20 33 , 36 , 37 , 40 53 , 55 , 56 , 286 293 ]), chest X-ray for routine checkup or follow-ups [ 78 – 113 , 118 120 , 339 343 ], trauma CT in patients without clinical symptoms or as repeat scans [ 227 232 , 287 , 314 322 ], and skeletal X-rays in non-traumatic pain or in fracture follow-ups [ 132 , 138 , 139 , 151 – 156 , 160 167 , 169 , 323 337 ]. The following were the most frequently reported low-value examinations: imaging in low back pain [ 121 131 ] and knee MRI without red flags [ 121 , 141 147 ], staging and follow-up in several types of cancer (X-ray, CT, MRI and nuclear medicine) [ 58 , 116 , 172 , 199 203 , 209 , 234 262 ], abdominal CT in self-limiting episode of suspected urolithiasis [ 190 , 204 206 ], chest CTA [ 210 216 ] and ultrasound lower limb veins in patients with low risk of thrombosis [ 217 221 ] were most prominent among adult populations.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these examinations already have established referral criteria or have recommendations against them in the Choosing Wisely list, however this review show that these are still being used in clinical practice, and more examinations might need referral guidelines. The most commonly practices reported as low-value was head CT in several clinical queries (especially related to minor head injury [ 20 33 , 36 , 37 , 40 53 , 55 , 56 , 286 293 ]), chest X-ray for routine checkup or follow-ups [ 78 – 113 , 118 120 , 339 343 ], trauma CT in patients without clinical symptoms or as repeat scans [ 227 232 , 287 , 314 322 ], and skeletal X-rays in non-traumatic pain or in fracture follow-ups [ 132 , 138 , 139 , 151 – 156 , 160 167 , 169 , 323 337 ]. The following were the most frequently reported low-value examinations: imaging in low back pain [ 121 131 ] and knee MRI without red flags [ 121 , 141 147 ], staging and follow-up in several types of cancer (X-ray, CT, MRI and nuclear medicine) [ 58 , 116 , 172 , 199 203 , 209 , 234 262 ], abdominal CT in self-limiting episode of suspected urolithiasis [ 190 , 204 206 ], chest CTA [ 210 216 ] and ultrasound lower limb veins in patients with low risk of thrombosis [ 217 221 ] were most prominent among adult populations.…”
Section: Discussionmentioning
confidence: 99%
“…It can also have negative health impacts for patients such as delirium and missed medications or meals. This change in practice has occurred despite available research evidence suggesting that the risk of significant bleeding and death is very low …”
Section: Introductionmentioning
confidence: 99%
“…Several authors suggested that most of observed patients can be safely discharged without a second CT scan, in the absence of clinical impairment, due to the low rates of delayed ICH occurring after 24 h from trauma. [ 38 39 40 41 42 43 ]…”
Section: Discussionmentioning
confidence: 99%